2007
DOI: 10.1892/07-058.1
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-Reactive Protein Concentration as an Indicator of Remission Status in Dogs with Multicentric Lymphoma

Abstract: CRP is useful in determining complete remission status after treatment with cytotoxic drugs. However, the individual variation between dogs means CRP concentration is not sufficiently different in other remission states to permit its use in monitoring progression of the disease. Greater reliability in determining remission status might be achieved by combining CRP concentration with other serum markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 24 publications
5
57
0
1
Order By: Relevance
“…The present study showed significantly increased serum AGP levels in dogs with carcinoma, sarcoma, and lymphoma (round cell tumor), when compared with healthy dogs. This supports the findings of Ogilvie et al (1993), Hahn et al C-reactive protein, serum amyloid A, and haptoglobin are all acute-phase proteins (APPs) like AGP, and are known to be elevated in some mammary tumors and lymphomas in dogs (Nielsen et al 2007;Tecles et al 2009). However, the dynamics of these APPs in other tumors are not well known.…”
Section: Discussionsupporting
confidence: 89%
“…The present study showed significantly increased serum AGP levels in dogs with carcinoma, sarcoma, and lymphoma (round cell tumor), when compared with healthy dogs. This supports the findings of Ogilvie et al (1993), Hahn et al C-reactive protein, serum amyloid A, and haptoglobin are all acute-phase proteins (APPs) like AGP, and are known to be elevated in some mammary tumors and lymphomas in dogs (Nielsen et al 2007;Tecles et al 2009). However, the dynamics of these APPs in other tumors are not well known.…”
Section: Discussionsupporting
confidence: 89%
“…However, as a biomarker it is not disease specific. 3,[11][12][13] Coupling biomarkers for rapid cell proliferation and inflammation has a strong relevance to the neoplastic process and malignant transformation. Chronic inflammation has been shown to predispose a patient to the development of neoplasia.…”
Section: Tests For Lymphoma Veterinary Diagnostics Institute Tkcanine1mentioning
confidence: 99%
“…12 In human oncology, serum CRP concentrations have shown potential as diagnostic and prognostic markers in various neoplastic diseases, including epithelial ovarian cancer, thymic cell carcinoma, pancreatic cancer, colorectal cancer, renal cell carcinoma, and multiple myeloma. 12 Specifically, in lymphoma it has been used as a prognostic factor and as a marker for remission and relapsed disease and correlated with stage and substage of affected patients. 12,13,19 A 2005 study by Tecles and colleagues 13 evaluated serum concentrations of APPs haptoglobin, ceruloplasmin, serum amyloid A, and CRP in dogs.…”
Section: Sensitest/petscreen/tri-screen/canine Lymphoma Blood Testmentioning
confidence: 99%
See 2 more Smart Citations